i-Code Studio: A Configurable and Composable Framework for Integrative AI - Fang, Yuwei; Khademi, Mahmoud; Zhu, Chenguang; Yang, Ziyi; Pryzant, Reid; Xu, Yichong; Qian, Yao; Yoshioka, Takuya; Yuan, Lu; Zeng, Michael; Huang, Xuedong (The 2024 Conference on Empirical Methods in Natural Language Processing (EMNLP24 Demo Track), 2024)
Artificial General Intelligence (AGI) requires comprehensive understanding and generation capabilities for a variety of tasks spanning different modalities and functionalities. Integrative AI is one important direction to approach AGI, through combining multiple models to tackle complex multimodal tasks. However, there is a lack of a flexible and composable platform to facilitate efficient and effective model composition and coordination. In this paper, we propose the i-Code Studio, a configurable and composable framework for Integrative AI. The i-Code Studio orchestrates multiple pre-trained models in a finetuning-free fashion to conduct complex multimodal tasks. Instead of simple model composition, the i-Code Studio provides an integrative, flexible, and composable setting for developers to quickly and easily compose cutting-edge services and technologies tailored to their specific requirements. The i-Code Studio achieves impressive results on a variety of zero-shot multimodal tasks, such as video-to-text retrieval, speech-to-speech translation, and visual question answering. We also demonstrate how to quickly build a multimodal agent based on the i-Code Studio that can communicate and personalize for users. The project page with demonstrations and code is at https://i-code-studio.github.io/.